La didattica a distanza durante il lockdown in Italia: il punto di vista delle famiglie - Giordana Szpunar; Eleonora Cannoni; Anna Di Norcia (LED Edizioni Universitarie, 2021)
Lockdown due to Covid-19 sanitary emergency causes a sudden break for scholar, social, cultural activities and sports. The aim of this work was to highlight changes in habits of life for children and teenagers with a particular focus on school activities. An on-line questionnaire was administrated to 5022 parents of children aged from 3 to 18 years. Results showed that secondary schools were able to guarantee at least hours of on-line lessons for half of the ordinary timing of schools. For preschooler and primary school, it seems that the recommended attention to maintain relations between the class group was less respected. So it seems that, during lockdown, children and teenagers were exposed to poverty of education and deprivation of social relationships. Probably due to lack of an adequate training for teachers, distance learning did not favored didactics strategies different from the traditional ones above all for preschool and primary schools.